2019
DOI: 10.1525/collabra.230
|View full text |Cite
|
Sign up to set email alerts
|

When Your Boo Becomes a Ghost: The Association Between Breakup Strategy and Breakup Role in Experiences of Relationship Dissolution

Abstract: Ghosting, or avoiding technologically-mediated contact with a partner instead of providing an explanation for a breakup, has emerged as a relatively new breakup strategy in modern romantic relationships. The current study investigated differences in the process of relationship dissolution and post-breakup outcomes as a function of breakup role (disengager or recipient) and breakup strategy (ghosting or direct conversation) using a cross-validation design. A large sample of participants who recently experienced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
70
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(102 citation statements)
references
References 36 publications
(73 reference statements)
7
70
0
10
Order By: Relevance
“…Although the present study does not report such information, it is likely that lack of significant associations between ghosting and psychological correlates is related to the type of sentimental relationship. Former research has revealed that ghosting is a more widely used dissolution strategy in short-term relationships characterized by less commitment [12]. Long-term relationships are associated with suffering more distress after breaking up than short-term ones [52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the present study does not report such information, it is likely that lack of significant associations between ghosting and psychological correlates is related to the type of sentimental relationship. Former research has revealed that ghosting is a more widely used dissolution strategy in short-term relationships characterized by less commitment [12]. Long-term relationships are associated with suffering more distress after breaking up than short-term ones [52].…”
Section: Discussionmentioning
confidence: 99%
“…These authors also reported firmer destiny beliefs (i.e., steady and invariable relationships). Koessler, Kohut, and Campbell [12] discovered that the relationships which ended via ghosting were more short term and characterized by less commitment than those terminated by direct conversation. Navarro et al [11] revealed that ghosting behaviors are linked to using online dating sites/apps, the time spent on online dating apps/sites, online surveillance, and more short-term relationships.…”
Section: Ghosting and Breadcrumbing: Definition And Researchmentioning
confidence: 99%
“…Ghosting occurs through one technological means or many; e.g., not responding to phone calls or text messages, no longer following partners or blocking partners on social networks platforms. Ghosting differs from other relationship dissolution strategies insofar as an explicit explanation or announcement of termination to the breakup receiver is lacking (Koessler, Kohut & Campbell, 2019) The term ghosting was originally posted in the 2006 Urban dictionary, has gained increasing attention in recent times, and was chosen as one of the top words in 2015 by the Collins English Dictionary (The Telegraph, 2015). Then in 2016, a new relationships trend in the dating scene emerged: "breadcrumbing" (The New York Times, 2016).…”
Section: Ghosting and Breadcrumbingmentioning
confidence: 99%
“…Although flirting, ignoring someone or dissolving a relationship are no recent phenomena, the proliferation of dating apps, such as Tinder, Grindr, eHarmony or Bumble, influences traditional processes of relationship dissolution or maintenance (Koessler et al, 2019). There is still very little empirical evidence for new flirting, ignoring, rejection or breakup strategies.…”
Section: Research Gaps: Lack Of Empirical Studies On Ghosting Breadcrumbing and Online Dating Usementioning
confidence: 99%
“…V akademickej sfére sa čoraz viac dostáva do povedomia problematika ghostingu, ktorá si nachádza svoje zastúpenie aj v komunikácii verejnej správy s obyvateľmi krajiny a v komunikácii samosprávy so svojimi obyvateľmi. Teoretické základy pre ghosting položili LeFebre (2017),Koessler (2018), Friedman et al (2018),Richardson (2017), ale aj Vagaš a Miško (2018), ktorí sa venovali problematike ghostingu vo vzťahoch medzi mužmi a ženami, medzi politickými stranami v krajine alebo na pracovisku v pracovných vzťahoch ľudských zdrojov v organizácii. Za ghosting môžeme považovať akékoľvek vyhýbavé správanie, prerušenie akejkoľvek komunikácie, ktoré vedie ku ignorancii danej osoby bez upozornenia.…”
unclassified